Agroecological practices characterization survey - Orjuela Ramirez, Guillermo Alejandro; Buritica Casanova, Alexander; Gonzalez Rojas, Maria Carolina (2024)
The agroecological practices characterization survey provides quantitative information from 850 farmers in Peru, from the Ucayali region, in the Padre Abad and Coronell Portillo districts. This survey disaggregates information at the plot level and includes information on agroecological practices and socioeconomic characterization.